A recepção de Jorge Amado no New York Times (1945-2001) - Sperb, Paula (My University, 2018)
This work aims to investigate the reception of the brazilian writer Jorge Amado in the United States, more specifically in the north-american newspaper New York Times. For this objective, one hundred and fifty-one articles published in the newspaper were found, between 1945 and 2001. For a better understanding of the author's reception, we presente the history of political and cultural relations between Brazil and United States during the period before World War II until the end of it. With the so-called "good neighbor policy", both countries have approached. The narrowing of ties is a factor that contributed to Jorge Amado's entry into the north-american literary polysystem in 1945, with the book The violent land. The debut book was published by the prestigious publisher Alfred Knopf. The writer's editorial trajectory, which went through Avon Books and Bantam, is also presented. The communist militancy of Jorge Amado was monitored and registered by the CIA (Central Intelligence Agency), fact verified in twenty-two reports produced by the organ during the Cold War. The documents corroborate the hypothesis that the writer's political ties caused him to occupy a peripheral position in the polysystem for seventeen years. Only in 1962, a second book by the author, Gabriela, was published in the United States, resulting in a commercial success and placing the writer in a position of centrality in the polysystem. From the 1960s to the 1980s, Jorge Amado was often associated with the boom of latin american literature. In this last decade, the writer was rediscovered: the book Showdown received the largest amount, until then, by the authors rights for a foreign book. Throughout his reception, Jorge Amado has always been mentioned in the New York Times as a synonym and symbol of Brazil.
Este trabalho tem como objetivo investigar acerca da recepção do escritor brasileiro Jorge Amado nos Estados Unidos, mais especificamente no jornal norte-americano New York Times. Para tanto, foram levantados cento e cinquenta e um artigos publicados no referido periódico, entre os anos de 1945 e 2001. Para uma melhor compreensão da recepção do autor, primeiramente, apresenta-se um histórico das relações políticas e culturais entre Brasil e Estados Unidos no período que antecede a Segunda Guerra Mundial até o final desta. Com a chamada “política da boa vizinhança”, ambos países se aproximaram. O estreitamento dos laços é um fator que contribuiu para entrada de Jorge Amado no polissistema literário norte-americano, em 1945, com o livro Terras do sem-fim. O livro de estreia foi publicado pela prestigiada editora Alfred Knopf. A trajetória editorial do escritor, que passou pelas editoras Avon Books e Bantam, também é apresentada. A militância comunista de Jorge Amado foi acompanhada e registrada pela CIA (Central Intelligence Agency), fato verificado em vinte e dois relatórios produzidos pelo órgão durante a Guerra Fria. Os documentos corroboram a hipótese de que os laços políticos do escritor fizeram com que ocupasse posição periférica no polissistema durante dezessete anos. Apenas em 1962, um segundo livro do autor, Gabriela, foi publicado nos Estados Unidos, resultando em um sucesso comercial e colocando o escritor em posição de centralidade no polissistema. Dos anos 1960 aos anos 1980, Jorge Amado foi frequentemente associado ao boom da literatura latino-americana. Nesta última década, o escritor foi redescoberto: o livro Tocaia grande recebeu a maior quantia, até então, pelos direitos autorais de um livro estrangeiro. Ao longo de sua recepção, Jorge Amado sempre foi mencionado no New York Times como sinônimo e símbolo de Brasil.
Keywords: Amado, Jorge, 1912-2001; Jornalismo e literatura; Literatura brasileira - Crítica e interpretação; Journalism and literature; Brazilian literature - Criticism and interpretation